2013
DOI: 10.1155/2013/914748
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Gamma-Glutamyltransferase Is Strongly Determined by Acylation Stimulating Protein Levels Independent of Insulin Resistance in Patients with Acute Coronary Syndrome

Abstract: Background. Steatosis is a manifestation of the metabolic syndrome often associated with release of liver enzymes and inflammatory adipocytokines linked to cardiovascular risk. Gamma-glutamyltransferase (GGT) is one sensitive liver marker recently identified as an independent cardiovascular risk factor. Mechanisms involved in enhanced hepatic lipogenesis causing steatosis are not yet identified and are usually linked to insulin resistance (IR). Acylation stimulating protein (ASP), a potent lipogenic factor, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Many studies have demonstrated that alanine aminotransferase (ALT), aspartate aminotransferase (AST) and gamma-glutamyl transferase (GGT) levels as liver markers, independently predict type 2 diabetes [9] [10], metabolic syndrome [11]- [13], and CVD [14] [15]. These markers have been shown to be associated with indirect measurements of insulin resistance including fasting insulin levels [13] [16] and HOMA-IR [9] [17]- [19]. However, there are few studies that demonstrate a relationship between changes in liver markers and insulin resistance after exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that alanine aminotransferase (ALT), aspartate aminotransferase (AST) and gamma-glutamyl transferase (GGT) levels as liver markers, independently predict type 2 diabetes [9] [10], metabolic syndrome [11]- [13], and CVD [14] [15]. These markers have been shown to be associated with indirect measurements of insulin resistance including fasting insulin levels [13] [16] and HOMA-IR [9] [17]- [19]. However, there are few studies that demonstrate a relationship between changes in liver markers and insulin resistance after exercise.…”
Section: Introductionmentioning
confidence: 99%